The Effects of Nordic hamstring exercise on the different surface to muscle strength, proprioception and postural sway in healthy adult - Bong , Eun-Bi; Jung , Hyun-Ji; Jung , Hyun-Ji; Jeon, Jeong woo; Hong , Ji-Heon; Yu , Jae-Ho; Kim , Jin- Seop; Lee, Dong-Yeop (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to investigate the changes of postural sway and eccentric muscle strength and proprioception on an unstable surface during the Nordic Hamstring Exercise (NHE).Methods/Statistical analysis: Forty male adults participated in this study. All subjects are randomized into groups of stable and unstable surfaces. NHE is administered three times a week for four weeks, with two measurements of muscle strength, proprioception, and postural sway before and after exercise. Paired t-tests were used to compare the differences before and after intervention in the group, and independent t-tests were used to compare the difference of effects between groups.Findings: As a result of this study, there was a significant difference in the joint position sense of knee and hip in the comparison between groups(p